SAYING “SAMPUN” IN THE JAVANESE SPEECH COMMUNITY: BETWEEN POLITENESS STRATEGY AND SINCERITY - Sri Waluyo (STMIK BINA PATRIA, 2018)
This paper attempts to reveal the illocutionary act and politeness strategy among the Javanese speech community behind the word “sampun” or “already”. Four different conversations in two different situations were noted based on the writer’s observations. Two conversations between a Basa Jawa teacher and his students were noted in two different classrooms in a junior high school. While, the other two conversations were observed in a house with a Javanese host who was visited by two different Javanese guests in two different occasions. The findings revealed that the word “sampun” in the school which was uttered by the students to respond the teacher’s question was insincere and contained positive politeness and indirect illocutionary act. However, the finding was different in the host and guest conversation where the first guest was sincere when uttering ”sampun” while the other was not so sincere due to the local wisdom of the politeness strategy admitted by the Javanese speech community. Keywords: “Sampun”, Illocutionary Act, Politeness Strategy, Speech Community